PENGARUH BRAND COMMUNITY DAN WORD OF MOUTH TERHADAP KEPUTUSAN PENGGUNAAN JASA SEWA PERALATAN OUTDOOR ATAP BUMI ADVENTURE - Ikhsan Baihaqy; Purwanti (Journal of Research and Publication Innovation, 2025)
This study aims to determine the influence of brand community (X1) and word of mouth (X2) on the decision to use (Y) Atap Bumi Adventure outdoor equipment rental services in Cisauk. The research method used is quantitative with an associative approach. The research population is 376 consumers of Atap Bumi Adventure, and the sample determination uses the probability sampling method and the sampling technique uses the random sampling method. The sample determination uses the Slovin formula with a 5% error rate, with a sample result of 79 people. Data were collected through questionnaires and analyzed using simple and multiple linear regression, correlation coefficients, and determination coefficients, as well as classical assumption tests (normality, multicollinearity, autocorrelation, and heteroscedasticity) and significance tests (partial and simultaneous) with the help of SPSS version 25. The results of the study indicate that brand community (X1) has a positive and significant effect on the decision to use (Y) partially, with a calculated t-value (7.462) > t-table (1.665) and significance (0.000) < 0.05. The contribution of brand community to the decision to use is 86.8%, word of mouth (X2) does not have a positive and significant influence on the decision to use (Y) partially, with a calculated t-value (0.531) < t-table (1.665) and significance (0.597) > 0.05. The contribution of word of mouth to the decision to use is 77.3%, brand community (X1) and word of mouth (X2) simultaneously have a positive and significant influence on the decision to use (Y), with a calculated F-value (255.707) > F-table (3.117) and significance (0.000) < 0.05. The contribution of both variables together to the decision to use is 86.7%, while the remaining 13.3% is influenced by other factors. The conclusion of this study is that brand community has an important role in influencing consumer decisions, while word of mouth partially does not show a significant influence. However, when both variables are combined, both significantly influence the decision to use Atap Bumi Adventure's outdoor equipment rental services.